Exploring Clitoria ternatea (Blue pea) herbal tea: A potent beverage with antioxidant and α- amylase inhibitory activity (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Diabetes is a global health challenge, with oxidative stress playing a crucial role in its development. Incorporating functional foods derived from medicinal plants is an effective approach to diabetes management. This study aimed to formulate and evaluate a composite herbal tea using Clitoria ternatea (Bluepea) as the primary ingredient, combined with Mentha arvensis (Mint), Cymbopogon citratus (Lemongrass), and Rosa centifolia (Rose petals) known for their pharmacological properties. Three herbal tea formulations were developed and subjected to sensory analysis to select the most acceptable formulation, which was then subjected to proximate nutrient analysis, phytochemical analysis, DPPH assay, microbial analysis, and in vitro α-amylase inhibitory activity. Statistical analysis was performed using SPSS version 26. Blue pea and lemongrass formulation was the most acceptable formulation, with one-way ANOVA results reporting statistically significant differences (P